PERANCANGAN USER INTERFACE DALAM MEMBANGUN MEDIA PEMBELAJARAN BAHASA INGGRIS (STUDI KASUS : NARRATIVE TEXT & STORYTELLING PADA SMP NEGERI SATU ATAP 2 TUNGKAL ULU) - Mulyati , Sri; Puad, Lailyn; Silvianti, Marini (JURNAL AKADEMIKA, 2024)
Technology is currently needed in all fields, especially in the education sector. Technology in education can be used for all kinds of activities, one of them is teaching and learning. On this situation, technology can be used to build interactive learning media, which must also be paired with an attractive user interface. Therefore, it can give a new impression to students and increase their enthusiasm for learning. In building learning media with an attractive user interface, supporting software can be used, such as Adobe Flash and Canva since this learning media requires attractive images, colors and animations to eliminate students' feelings of boredom. The school as the destination for this thesis research is SMP Negeri Satu Atap 2 Tungkal Ulu which still used a learning method that could be said to be monotonous, sometimes they still used a system where students only listened and took notes without any other activities. This situation made students tend to be easy getting bored. One interesting subject for learning is English, with material taken is narrative text and storytelling. This learning media contains a menu of instructions, materials, discussion videos, quizzes and evaluations, assisted by a good user interface. The development of this learning media turned out to be able to help raising students' enthusiasm, as evidenced by the questionnaire that was carried out which gave a result of 72.3% and was included in the satisfactory category.